The impact of long-term vitamin D deficiency on the offspring metabolic health and cognitive function via epigenetic changes - Madi, Gulden (2023)
Exposure to adequate Vitamin D during early development is crucial for neurodevelopment. However, the prevalence of Vitamin D deficiency (VDD) among women of childbearing age is on the rise. This study aims to investigate the impact of maternal VDD on postnatal neurodevelopment and delve into potential underlying mechanisms.